1975
DOI: 10.1111/j.1476-5381.1975.tb07598.x
|View full text |Cite
|
Sign up to set email alerts
|

Displacement by Metiamide of the Dose‐response Curves to Pentagastrin and Methacholine in the Conscious Rat

Abstract: 1 The effect of a specific histamine H2-receptor antagonist, metiamide, on the acid dose-response curves for pentagastrin or methacholine was studied in rats provided with Heidenhain pouches. 2 Metiamide induced a shift to the right of the dose-response curve to pentagastrin and lowered the maximal secretion.3 In contrast, metiamide only increased the ED50 for methacholine but did not alter the calculated maximal response. 4 The effect of metiamide on pentagastrin and methacholine-induced secretion is in agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The reduction of the maximal response to gastrin in the presence of metiamide (Figure 4) is compatible with a non-competitive type of inhibition, and is similar to results obtained in vivo using pentagastrin in the Heidenhain pouch rat (Lundell, 1975), and by Black (1973) using the Heidenhain pouch dog. However metiamide has been shown to act like a competitive antagonist at H2-receptors (Parsons, 1973;Bunce & Parsons, 1976), and this situation led Black (1973) to postulate that canine gastric mucosa possesses two types of gastrin receptor.…”
Section: Discussionsupporting
confidence: 86%
“…The reduction of the maximal response to gastrin in the presence of metiamide (Figure 4) is compatible with a non-competitive type of inhibition, and is similar to results obtained in vivo using pentagastrin in the Heidenhain pouch rat (Lundell, 1975), and by Black (1973) using the Heidenhain pouch dog. However metiamide has been shown to act like a competitive antagonist at H2-receptors (Parsons, 1973;Bunce & Parsons, 1976), and this situation led Black (1973) to postulate that canine gastric mucosa possesses two types of gastrin receptor.…”
Section: Discussionsupporting
confidence: 86%
“…In addressing the question of whether gastric acid secretion modifies chemosensory afferent inputs from the gastric lumen, we used cimetidine and omeprazole at doses known to effectively suppress basal and stimulated gastric acid secretion in the rat: cimetidine at the dose of 40 mol/kg (5), omeprazole at the dose of 20 mol/kg (24), and pentagastrin at a dose (195 mol/kg) that maximally increases gastric acid secretion in the rat (26). Because cimetidine failed to alter the NTS response to intragastric NH 4 OH, it can be ruled out that NH 4 OH led to stimulation of vagal afferents because it facilitated the backdiffusion of luminal acid through the NH 4 OH-compromised gastric mucosa or because it increased gastrin and gastric acid secretion (30).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies using histamine H2-receptor antagonists have shown that these compounds inhibit acid secretion in response to histamine, gastrin (or pentagastrin) and cholinergic stimulation (Parsons, 1975). However the acid response to cholinergic stimulation is more resistant to inhibition by H2-receptor antagonists than the response to pentagastrin (Black, 1973;Lundell, 1975a).…”
Section: Introductionmentioning
confidence: 99%